Girdin Phosphorylation Is Crucial for Synaptic Plasticity and Memory: A Potential Role in the Interaction of BDNF/TrkB/Akt Signaling with NMDA Receptor - Nakai, Tsuyoshi (J Neurosci, 2014)
Synaptic plasticity in hippocampal neurons has been thought to represent a variety of memories. Although accumulating evidence indicates a crucial role of BDNF/TrkB/Akt signaling in the synaptic plasticity of the hippocampus, the mechanism by which Akt, a serine/threonine kinase, controls activity-dependent neuronal plasticity remains unclear. Girdin (also known as APE, GIV, and HkRP1), an actin-binding protein involved both in the remodeling of the actin cytoskeleton and in cell migration, has been identified as a substrate of Akt. Previous studies have demonstrated that deficit of neuronal migration in the hippocampus of Girdin-deficient (Girdin(−/−)) mice is independent on serine phosphorylation of Girdin at S1416 (Girdin S1416) by Akt. In the present study, we focused on the role of Girdin S1416 phosphorylation in BDNF/TrkB/Akt signaling associated with synaptic plasticity. We found that Girdin in the hippocampus was phosphorylated at S1416 in an activity-dependent manner. Phosphorylation-deficient knock-in mice (Girdin(SA/SA) mice), in which S1416 is replaced with alanine, exhibited shrinkage of spines, deficit of hippocampal long-term potentiation, and memory impairment. These phenotypes of Girdin(SA/SA) mice resembled those of Girdin(+/−) mice, which have 50% loss of Girdin expression. Furthermore, Girdin interacted with Src kinase and NR2B subunit of NMDA receptor, leading to phosphorylation of the NR2B subunit and NMDA receptor activation. Our findings suggest that Girdin has two different functions in the hippocampus: Akt-independent neuronal migration and Akt-dependent NR2B phosphorylation through the interaction with Src, which is associated with synaptic plasticity in the hippocampus underlying memory formation.